The Effect of Academic Supervision on the Improvement of the Pedagogic Competence of MAN (Madrasah Aliah Negeri/Indonesia) Jeneponto teachers. - Saleh, Sirajuddin; Rahmadani, Sri; Jamaluddin (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Supervision is a set of activities carried out by supervisors to assist teachers in developing their abilities, especially in pedagogical abilities. This study aims to determine the effect of academic supervision on increasing the pedagogic competence of MAN (Madrasah Aliah Negeri/Indonesia) Jeneponto teachers. This research is a quantitative study with a research population of 70 teachers and the samples in this study were 70 teachers. Data collection techniques used through questionnaires, interviews, and documentation. The data obtained from the research were processed using data analysis consisting of descriptive analysis techniques and inferential statistical analysis. The results showed that the Academic Supervision of MAN Jeneponto was in the very high category with a percentage rate of 85, 77 percent, and for the pedagogical competence of MAN Jeneponto teachers in the very good category with a percentage rate of 85.6 percent which means the level of the relationship was in the very strong category. It can be concluded that there is a positive and significant effect of academic supervision on the pedagogic competence of MAN Jeneponto teachers.